Pembaharuan Data Profil Desa Bumirejo Sebagai Dasar Menetapkan Sasaran Program Pembangunan Desa - Rohmat Junarto; M. Nazir Salim; Harvini Wulansari (Universitas Bengkulu, 2023)
The rural development process in Indonesia ideally translates village character and responds to community needs. However, some of these villages have not prepared and updated village profile data based on real-world conditions in order to provide a complete picture of the village's character. The purpose of this paper is to photograph the development of Bumirejo Village so that it can be used to set development program targets and assess the effectiveness of village development. This community service activity employs qualitative methods. Data collection techniques such as observational studies and in-depth interviews and data analysis employs narrative analysis. As part of the village government, this activity resulted in a village profile book containing basic family data, potential, and regional development of each hamlet.